Factors Affecting The Diarrhea Occurances On U5 Children In Manyak Payed Public Health Services Aceh Tamiang - Marniati, Marniati; Pertiwi, Artika; Rahmayani, Rahmayani (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Diarrhea is the number one cause of the death on U5 children among other 10 diseases in Indonesia. The bad sanitation is the most significant factor that causes the occurrences of diarrhea, Therefore, the interaction among diseases, human and other environment factors that led to the diarrhea occurrences should be properly addressed in the diarrhea prevention programs. The environment factors, like water, foods, flies and insects, Enterobacter, intestinal paracites, viruses, fungus and sal chemicals have also considerable roles to that. The objective of this paper is to examine factors that influence the diarrhea occurrences on U5 children in Manyak Payed Public Health Services, Aceh Tamiang. This research uses an analytical approach with population of 89 people per March 2014. The sample is 47 people and is collected using accidental sampling technique. The data is collected through questionnaires that are distributed to Manyak Payed Public Health Services, from 28 May to 6 June 2014. The result shows that of 27 respondents who live in an unhealthy environment, 77.8% of them haveÂ  suffered from diarrhea with p value of 0.001 (p<0.05). While, 71% of 31 respondents with lower economic status alsoÂ  experienced diarrhea with p value of 0.007 (p<0.05) and 73.9% of 23 respondents with limited knowledge on diarrhea have alsoÂ  experienced diarrhea with p value of 0.029 (p<0.05). Thus, it can be concluded that there is a relationship between environment, economic status and parentsâ knowledge and the diarrhea occurrences on U5 children.